2009
DOI: 10.1016/j.rser.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Electricity generation development of Eastern Europe: A carbon technology management case study for Poland

Abstract: Energy and electricity in particular, are of unquestionable value for the welfare of all modern societies. The electricity sectors of Eastern European countries have undergone several phases of development between the post-WWII days within the CEMA and USSR frameworks and today's EU and global energy and environmental regimes. The present paper examines the progress of the Polish electricity sector throughout the last decades, providing useful information regarding not only the technical generation and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…The continuous steep decline in China's carbon intensity per economic output (Section 3) is a result of central organization and robust policies applied in the country [78,79]. Discussing carbon intensity per energy input, the divergence that the Philippines show has its origins in the increasingly coal reliant fuel mix between 1994-2014 which resulted in an eight-fold increase in CO2 emissions originating from its coal fuel mix and the use of blast furnace gas fuel [80].…”
Section: Carbon Intensity Resultsmentioning
confidence: 99%
“…The continuous steep decline in China's carbon intensity per economic output (Section 3) is a result of central organization and robust policies applied in the country [78,79]. Discussing carbon intensity per energy input, the divergence that the Philippines show has its origins in the increasingly coal reliant fuel mix between 1994-2014 which resulted in an eight-fold increase in CO2 emissions originating from its coal fuel mix and the use of blast furnace gas fuel [80].…”
Section: Carbon Intensity Resultsmentioning
confidence: 99%
“…Those changes included, among others, partial privatization of the industry, improvement of the energy efficiency of the companies as a result of initiated restructuring actions, as well as a gradual transition of the energy policy increasing the role of oil, gas and renewables together with popularization of cogeneration (Chalvatzis, 2009;EU, 2012).…”
Section: The Selected Aspects Of Poland's Energy Policymentioning
confidence: 99%
“…The Environmental Agenda stresses the need to shift energy sources towards less emissive ones, such as natural gas, nuclear energy and renewable energy. In the case of natural gas, the Russian Federation can be considered as the main supplier of this fuel to Poland, which means that the strategy would undermine the country's energy security [2]. There are no nuclear power plants functioning in Poland, and there is also no social acceptance for their construction (opinion polls showed that 52% of respondents would object to the construction of such a power plant and 70% would object if a power plant were to be built near their place of residence [3]).…”
Section: Introductionmentioning
confidence: 99%